Description and Ecology of A New Cavernicolous, Arachnophilous Thread-legged Bug (Hemiptera: Reduviidae: Emesini) from Kartchner Caverns, Cochise County, Arizona - Pape, Robert B. (Zootaxa, 2013)
A new cavernicolous, arachnophilous thread-legged bug (Phasmatocoris labyrinthicus sp. nov.; Reduviidae: Emesini) is described from Kartchner Caverns, a limestone cavern in Kartchner Caverns State Park near Benson, Arizona, USA. Cavernicolous emesines are recorded from caves in many parts of the world and are distributed across several genera, but are generally uncommon. P. labyrinthicus shows no obvious troglomorphy but ecological evidence suggests it is, at minimum, a cave-limited troglophile. The species seems to be low-humidity intolerant, due to its occurrence in a cave within a desert region, effectively confines the population to the cave, and the species may thus actually be troglobitic by default. Arachnophily in emesines is more common, including in Phasmatocoris Breddin, but has been previously documented in only a single cavernicolous species, Bagauda cavernicola Paiva, reported from India, Malaysia and Sri Lanka. However, unlike P. labyrinthicus, B. cavernicola is apparently not morphologically adapted for its arachnophilous association. P. labyrinthicus is the only known troglophilic emesine that is also a morphologically adapted and behaviorally functional arachnophile. The only other known cavernicolous Phasmatocoris (P. xavieri Gil- Santana, Alves, Barrett and Costa) is recorded from a sandstone cave in Brazil. P. xavieri exhibits morphological features indicative of a potentially arachnophilous habit, but its ecology has not been studied. Adults of P. labyrinthicus share characteristics with the species Phasmatocoris praecellens Bergroth, P. minor McAtee and Malloch, P. xavieri, P. spectrum Breddin, and P. rapax McAtee and Malloch. Phasmatocoris is primarily a Neotropical genus and the discovery of P. labyrinthicus represents a significant range extension for the genus, being the first Nearctic species identified, with its geographically nearest relative an undescribed species from Mazatlan, Mexico, over 1,000 km to the south.